Effect of pH on the Adsorption of Uranyl Ions by Peat Moss - Liu Zhirong; Zhou Shaoqi (Adsorption Science & Technology)
The removal of uranyl ions from aqueous solutions with peat moss was investigated by batch methods. The effects of factors such as the pH, ionic strength, contact time, peat moss dosage and humic acid concentration on uranyl ion adsorption were studied. The results indicated that the adsorption of uranyl ions onto peat moss increased with increasing pH within the range 2–6, with higher humic acid concentrations and with decreasing ionic strength. The kinetics of the adsorption process were well described by the Elovich equation, while the equilibrium adsorption isotherm was fitted reasonably well by the Freundlich adsorption model. The calculated fractal dimension of granular peat moss was 2.3384.